Country-specific and global shocks in the business cycle - Daniel Gross (Goethe University Frankfurt, Center for Financial Studies (CFS), 2001)
Industrial production in G7 countries is assumed to be driven by two exogenous disturbances. Those disturbances are identified in a VAR model so they can be interpreted as countryspecific and global supply shocks. The dynamic properties of the model are analyzed and the relative importance of each shock is measured. It is shown that the VAR model matches most of the theoretical predictions of standard intertemporal open-economy models. The identified structural disturbances are analyzed with regard to their impact on the current account and investment.
urn:nbn:de:hebis:30-9889
Keywords: E32; F41; 330; Country-Specific and Global Shocks; VAR; RBC